REAKSI PASAR TERHADAP PENGUMUMAN STOCK SPLIT TAHUN 2016 - A LA, NAJMY (Jurnal Ilmu Manajemen (JIM), 2017)
This study aims to know if there is market reaction before and after stock split annuncement year of 2016. This market reaction shows in is indicated by whether or not there is difference in abnormal return, trading volume activity, bid-ask spread, and security return variability.The types of research that used in this study are event study. The study used 16 firms as samples, selected by purposive sampling method. This study used 5 days before and 5 days after stock split as the observation period, using normality test (One Sample Kolmogorov Smirnov) and hypothesis test (Wilcoxon Signed Ranks Test). The result shows that there is no difference between abnormal return at before-after stock split period. There is no difference between trading volume activity at before-after stock split period. There is no difference between bid-ask spread at before-after stock split period. There is no difference between security return variability at before-after stock split period. This show that stock split annouchment does not have information content or it has but the market not to reacted to the announcement. Keywords:stock split, abnormal return, trading volume activity, bid-ask spread, and security return variability